2014
DOI: 10.1155/2014/534307
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Optothermal Properties of Iron Ditelluride Layered Structures in the Framework of the Lattice Compatibility Theory

Abstract: This study concerns structural and optothermal properties of iron ditelluride layered structures which were fabricated via a low-cost protocol. The main precursors were FeCl3· 6H2O and Fe2O3. After a heat treatment within a tellurium-rich medium at various temperatures (470°C, 500°C, and 530°C) during 24 h, classical analyses have been applied to the iron ditelluride layered structures. A good crystalline state with a preferential orientation of the crystallites along (111) direction has been recorded. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Crystalline size evaluation revealed that tin has a relative tendency to form SnxOy crystalline phases. At this level, the recently proposed Lattice Compatibility Theory [65][66][67][68][69][70][71][72][73][74][75] which was implied in similar cases, has been evoked. This theory, as mentioned in some recent studies [66][67][68][69][70][71][72][73][74] has been based on the interaction of doping-element lattice behavior versus host edifice.…”
Section: Discussion Of Sn Doped Nio Thin Films Growth Patterns In Termentioning
confidence: 99%
See 2 more Smart Citations
“…Crystalline size evaluation revealed that tin has a relative tendency to form SnxOy crystalline phases. At this level, the recently proposed Lattice Compatibility Theory [65][66][67][68][69][70][71][72][73][74][75] which was implied in similar cases, has been evoked. This theory, as mentioned in some recent studies [66][67][68][69][70][71][72][73][74] has been based on the interaction of doping-element lattice behavior versus host edifice.…”
Section: Discussion Of Sn Doped Nio Thin Films Growth Patterns In Termentioning
confidence: 99%
“…Fundaments to the Lattice Compatibility Theory [65][66][67][68][69][70][71][72][73][74][75] have been established by Petkova et al [65] in a study of Urbach tailing controversial behaviour in some nano-compounds as well as I-III-O2 ternary oxides instability at low temperatures. Elements of the Lattice Compatibility Theory have been presented later by Colantoni et al [66] Yumak et al [67], Ben Said et al [68], Gherouel et al [69], Haj Lakhdar et al [70], Boubaker et al [71][72][73], Ben Messaoud et al [74] and Mimouni et al [75].…”
Section: Discussion Of Sn Doped Nio Thin Films Growth Patterns In Termentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that in the energy range around 0.6-0.9 eV the spectral shape is clearly different from that typically observed for CuInTe 2 , where almost no absorption occurs [22]. Considering the fact that the FeTe impurity has its band-gap in the UV-vis region [23], the mentioned feature indicates a different electronic band structure for CuFeInTe 3 , with respect to that of CuInTe 2 , that is determined by the relatively high content of Fe 2+ atoms inserted in the crystal lattice. An indirect band-gap of 0.60 eV and a direct band-gap of 0.91 eV were found from Tauc´s plots [24,25], presented in Figure 5b.…”
Section: Optical Diffuse Reflectance Spectroscopy (Odrs)mentioning
confidence: 83%
“…In order to give evidence to the recorded incorporation of Cobalt ions within ZnO lattice preferentially over Chromium ions, a thorough investigation has been carried out within the framework of the Lattice Compatibility Theory LCT [36][37][38]. This theory has been early proposed by Petkova et al [36] in the skeleton of a study which tried to give an explanation to the spectacular Urbach tailing associated to some nanoscale lattice disordering which has been recorded in bismuth sillenites (BSO) and germanates (BGO) compounds.…”
Section: Lattice Compatibility Theory Analysesmentioning
confidence: 99%